The Effectiveness of Horticultural Occupational Therapy to Improve The Quality of Life in Schizophrenic Patients - Supiatun Supiatun; Aulia Iskandarsyah; Efri Widianti (Universitas Padjadjaran, 2021)
Schizophrenia is the most common mental disorder and is a serious problem in the world. Therapies that use natural systems such as horticultural occupational therapy, have been carried out in the implementation of mental health for centuries. However, in Indonesia, there is no scientific study of its effect on the quality of life (QOL) of those suffering from this illness. The research objective was to determine the effect of horticultural occupational therapy on improving the quality of life in schizophreniac patients at Muhammad Sani Hospital, Karimun district. The research was a quasi-experiment with two group pre-post tests. A total of 28 respondents were selected using the convenience sampling technique, then divided into intervention and control groups. Quality of life values was measured with WHOQOL-BREF, while the bivariate analysis used paired and independent t-tests. The result was a significant difference in the value within the intervention group at p = 0.000 (p <0.05), but there was none in the control at p = 0.189 (p> 0.05). For the independent t- test analysis, p-value physical and social domains were 0.001 (p <0.05) and 0.000 (p <0.05) respectively. This means that there was a significant difference in QOL in the two domains. Conclusion. Horticultural occupational therapy was effective in improving the quality of life in the patients, therefore, it becomes important to apply the results.Keywords: Horticultural occupational therapy, life quality, schizophrenia.